Późnośredniowieczny miecz ze stanowiska Lutomiersk-Koziówki 3a–c, pow. pabianicki - Kucypera, Paweł; Rybka, Krzysztof; Muzolf, Błażej (Acta Universitatis Lodziensis. Folia Archaeologica, 2012)
The paper deals with a late medieval longsword found during recent excavations at Lutomiersk-Koziówki, Pabianice County. The slender, hexagonal blade tapering acutely towards the point was identified as a late variaton of Oakeshott’s type XVII, the smooth-surfaced, slightly elongated pommel represents type T3, while the simple guard square in cross-section with convolute both ends pertains type 1a. The carried out analyzes of organic, heavily-mineralized residues found on the weapons surface were identified as remains of a scabbard and grip fittings. The handle cladding was made of ash wood and the scabbard slats of spruce wood. The scabbard was coated with sheepskin of high quality. A piece of fabric, which was lifted from the sword’s surface, was qualified as silk and considered as coming from an attire of Italian origin. Quantative chemical composition and possible method of blade’s manufacture are also presented and discussed, as well as the conservation process, which the artifact underwent.